A thousand days after the merger: Continued X-ray emission from GW170817. Issue 4 (12th October 2020) - Troja, E; van Eerten, H; Zhang, B; Ryan, G; Piro, L; Ricci, R; O'Connor, B; Wieringa, M H; Cenko, S B; Sakamoto, T
ABSTRACT: Recent observations with the Chandra X-ray telescope continue to detect X-ray emission from the transient GW170817. In a total exposure of 96.6 ks, performed between 2020 March 9 and 16 (935–942 d after the merger), a total of 8 photons are measured at the source position, corresponding to a significance of ≈5σ. Radio monitoring with the Australian Telescope Compact Array (ATCA) shows instead that the source has faded below our detection threshold (<33 $μ$ Jy, 3σ). By assuming a constant spectral index of β = 0.585, we derive an unabsorbed X-ray flux of ≈1.4 × 10 −15 erg cm −2 s −1, higher than earlier predictions, yet still consistent with a simple structured jet model. We discuss possible scenarios that could account for prolonged emission in X-rays. The current data set appears consistent both with energy injection by a long-lived central engine and with the onset of a kilonova afterglow, arising from the interaction of the sub-relativistic merger ejecta with the surrounding medium. Long-term monitoring of this source will be essential to test these different models.